The Kinematics ofActive Crustal Deformation in the Erkenek Segment of the Eastern Anatolian Fault Zone Using Comprehensive Surface Rupture Analysis from the February 6, 2023 Earthquake (Mw 7.7) - Akgun, Elif; Softa, Mustafa; Erol, Serap Colak; Aksoy, Ercan; Gurgoze, Serkan; Kocbulut, Fikret; Tatar, Orhan (Tmmob Jeoloji Muhendisleri Odasi, 2025)
The Eastern Anatolian Fault Zone (EAFZ) is a significantneotectonic feature in Anatolia, characterized as an active intra-continental left-lateral strike-slip fault. The EAFZ comprises two distinct parts: the southern branch, referred to as the main branch, and the northern branch. This study examines the surface rupture near & Ccedil;elikhan (Ad & imath;yaman) on the Erkenek Segment, which developed during the February 6, 2023 Pazarc & imath;k earthquake (Mw 7.7), occurring along the southern branch of the EAFZ. The primary emphasis of this study centers on preliminary findings derived from thorough geological investigations conducted on the surface fault rupture. Additionally, novel insights into seismic activity associated with the Erkenek Segment were revealed for the first time through meticulous field studies. In the studies, the maximum left-lateral displacement measured in the & Ccedil;elikhan section of the surface fracture was 3.25 meters, accompanied by a vertical slip of50 centimeters. The magnitude of left-lateral displacement decreased and attenuated moving northeastward from & Ccedil;elikhan. Based on kinematic analysis of slip data obtained from fault planes along the Erkenek segment, the deformation aligned with the segments' geometry and occurred within a strike-slip tectonic regime influenced by compressional stress predominantly oriented in NE-SW and NNW-SSE directions.
Keywords: East Anatolian Fault Zone; Erkenek segment; paleoseismology; paleostress; surface rupture